TUNGKUS ASI SEBAGAI VARIASI LOKAL POLITIK PENAUNGAN DI BATANG AI SEMASA PILIHAN RAYA NEGERI SARAWAK 2021 = TUNGKUS ASI AS A LOCAL VARIATION OF PATRONAGE POLITICS IN BATANG AI DURING THE 2021 SARAWAK STATE ELECTION - Anthony, Tutong; Neilson Ilan, Mersat (Penerbit Universiti Sains Malaysia, 2024)
This study explains the role of “tungkus asi” in strengthening the ruling party’s political power during the 2021 Sarawak State Election (SSE21) in Batang Ai. “Tungkus asi” is one of the local variations of patronage politics practised by the Iban at the grassroots level. During the 2016 Sarawak State Election “tungkus asi” played a role in the electoral victory of the candidate from Gabungan Parti Sarawak (GPS). In the SSE21, “tungkus asi” once again propelled the candidate from GPS to victory and thus strengthening the ruling party’s position in Batang Ai. This article looks at how “tungkus asi” was practised and its influence on the electoral support of the Iban towards the candidates. This article was based on a study conducted in Batang Ai which involved observation and interviews with the voters and “tuai rumah”. The study found that “tungkus asi” continued to play a prominent role in galvanising support from the voters. “Tungkus asi” remains relevant in the modern political era as it has become part and parcel of the political process and election among the Iban at the grassroots level. “Tungkus asi” not only consolidates GPS political power, but its practice also helps researchers and observers alike to understand the politics of patronage within the Iban voters.